PENGETAHUAN CALON PENGANTIN WANITA TENTANG IMUNISASI TETANUS TOXOID (TT) DI KANTOR URUSAN AGAMA (KUA) KECAMATAN PEUSANGAN KABUPATEN BIREUN - Rahmah, Siti; Malia, Anna; Nuraina, Nuraina (Jurnal Ilmiah Kesehatan Ibu dan Anak, 2022)
According to Health Law No. 23 of 1992, the "Healthy Paradigm" is implemented through several activities, including disease eradication. Efforts to eradicate infectious diseases are efforts to immunize. One of the government's steps to eliminate neonatal tetanus is by implementing the Tetanus Toxoid (TT) immunization program. The low coverage of TT illustrated the low interest of the community to carry out TT immunization, especially for prospective brides. The purpose of this study was to describe the knowledge of the prospective bride about catin immunization. This research was descriptive in nature, namely research to describe a phenomenon as a research subject. The population of this study were all prospective brides who registered themselves to be married at the KUA, totaling 34 respondents as samples. Research data analysis was carried out descriptively by looking at the percentage of data that had been collected and presented in a frequency distribution table. The results of the study showed that the knowledge of the bride and groom about catin immunization was obtained that there were 22 brides with good knowledge (65%), 10 people (29%) with sufficient knowledge and 2 brides with less knowledge (6%). Therefore, the knowledge of the prospective bride and groom about catin immunization at the KUA of Peusangan District, Bireuen Regency mostly had a good knowledge about catin immunization.